2012
DOI: 10.1128/jvi.00730-12
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the UAP56 Interaction Motif of Human Cytomegalovirus pUL69 to Its Murine Cytomegalovirus Homolog Converts the Protein into a Functional mRNA Export Factor That Can Substitute for pUL69 during Viral Infection

Abstract: Nucleocytoplasmic shuttling and interaction with the cellular mRNA export factor UAP56 are prerequisites for the mRNA export activity of human cytomegalovirus (HCMV) pUL69. Although the murine cytomegalovirus homolog pM69 shuttles, it fails to export mRNAs due to its inability to recruit UAP56. However, chimeric proteins comprising pM69 fused to N-terminal pUL69 fragments, including its UAP56 interaction motif, acquire mRNA export activity. Importantly, growth curves of recombinant HCMVs illustrate that such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 21 publications
(22 reference statements)
3
14
0
Order By: Relevance
“…7D, lanes 8 to 11 and 13). The latter observation confirms our previous finding that the combinatorial change of arginines 22,23,25, and 26 to alanine changes pUL69 into a UAP56-binding-deficient mutant (6,8,9). Interestingly, however, the arginines at positions 28 and 29 were not required for UAP56 interaction, since a mutant harboring the respective substitutions was coprecipitated by Myc-UAP56 (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…7D, lanes 8 to 11 and 13). The latter observation confirms our previous finding that the combinatorial change of arginines 22,23,25, and 26 to alanine changes pUL69 into a UAP56-binding-deficient mutant (6,8,9). Interestingly, however, the arginines at positions 28 and 29 were not required for UAP56 interaction, since a mutant harboring the respective substitutions was coprecipitated by Myc-UAP56 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…More recently, we extended these findings and showed that UAP56/URH49 recruitment is well conserved within the cytomegaloviral pUL69 homologs pCh69 of chimpanzee cytomegalovirus (CCMV) and pRh69 of rhesus cytomegalovirus (RhCMV). This activity correlated with stimulatory effects of the respective proteins on mRNA export analogously to pUL69 (8,9). The importance of UAP56/URH49 recruitment for HCMV multiplication was ultimately confirmed by the observation that recombinant cytomegaloviruses that had deletions or point mutations of the UAP56 interaction motif of UL69 (UL69⌬R1⌬RS and UL69mutUAP) exhibited a severe replication defect compared to wild-type virus (8).…”
Section: Importancementioning
confidence: 60%
See 3 more Smart Citations